Sistem Pakar Diagnosa Penyakit pada Tanaman Jambu Kristal Menggunakan Metode Dempster Shafer Berbasis Web - Saifu Rohman; Rina Mahmudati; Wiko Anang Ansoruloh (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2024)
The Crystal Guava plant can be attacked by several types of diseases. Diseases in crystal guava plants can cause significant losses in fruit production. Some pests and diseases that can attack crystal guava plants include fruit flies, bagworms, whiteflies, anthracnose, and red rust. Therefore, accurate and timely disease diagnosis is crucial in controlling and managing these diseases. In this study, an Expert System for Disease Diagnosis in Crystal Guava Plants Using the Dempster Shafer Method-Based Web was developed. The Dempster Shafer method calculates the likelihood of a disease attacking crystal guava plants based on the density probability values of each symptom. The results produced by this expert system include the type of disease, solution, and the percentage probability value of the disease, with an average accuracy of 83.33%. Hence, it can be concluded that the system can diagnose diseases in crystal guava plants effectively.